Antarctic environmental protection: strengthening the links between science and governance - Hughes, Kevin A; Constable, Andrew; Frenot, Yves; López-Martinez, Jerónimo; McIvor, Ewan; Njåstad, Birgit; Terauds, Aleks; Liggett, Daniela; Roldan, Gabriela; Wilmotte, Annick; Xavier, José C (Environmental Science & Policy, 2018)
The Antarctic has significant environmental, scientific, historic, and intrinsic values, all of which are worth protecting into the future. Nevertheless, the area is subject to an increasing level and diversity of human activities that may impact these values within marine, terrestrial and cryosphere environments. Threats to the Antarctic environment, and to the aforementioned values, include climate change, pollution, habitat destruction, wildlife disturbance and non-native species introductions. Over time, a suite of legally binding international agreements, which form part of the Antarctic Treaty System (ATS), has been established to help safeguard the Antarctic environment and provide a framework for addressing the challenges arising from these threats. Foremost among these agreements are the Protocol on Environmental Protection to the Antarctic Treaty and the Convention on the Conservation of Antarctic Marine Living Resources. Many scientists working in Antarctica undertake research that is relevant to Antarctic environmental policy development. More effective two-way interaction between scientists and those responsible for policy development would further strengthen the governance framework, including by (a) better communication of policy makers’ priorities and identification of related science requirements and (b) better provision by scientists of ‘policy-ready’ information on existing priorities, emerging issues and scientific/technological advances relevant to environmental protection. The Scientific Committee on Antarctic Research (SCAR) has a long and successful record of summarizing policy-relevant scientific knowledge to policy makers, such as through its Group of Specialists on Environmental Affairs and Conservation (GOSEAC) up to 2002, currently the SCAR Standing Committee on the Antarctic Treaty System (SCATS) and recently through its involvement in the Antarctic Environments Portal. Improvements to science-policy communication mechanisms, combined with purposeful consideration of funding opportunities for policy-relevant science, would greatly enhance international policy development and protection of the Antarctic environment.
Keywords: Antarktis; miljøvern

Ant-ICON - ‘Integrated Science to Inform Antarctic and Southern Ocean Conservation’: a new SCAR Scientific Research Programme - Hughes, Kevin A.; Santos, Mercedes; Caccavo, Jilda A.; Chignell, Stephen M.; Gardiner, Natasha B.; Gilbert, Neil; Howkins, Adrian; Van Vuuren, Bettine Jansen; Lee, Jasmine R.; Liggett, Daniela; Lowther, Andrew; Lynch, Heather; et al. (Antarctic Science, 2022)
Antarctic and Southern Ocean environments are facing increasing pressure from multiple threats. The Antarctic Treaty System regularly looks to the Scientific Committee on Antarctic Research (SCAR) for the provision of independent and objective advice based on the best available science to support decision-making, policy development and effective environmental management. The recently approved SCAR Scientific Research Programme Ant-ICON - ‘Integrated Science to Inform Antarctic and Southern Ocean Conservation‘ - facilitates and coordinates high-quality transdisciplinary research to inform the conservation and management of Antarctica, the Southern Ocean and the sub-Antarctic in the context of current and future impacts. The work of Ant-ICON focuses on three research themes examining 1) the current state and future projections of Antarctic systems, species and functions, 2) human impacts and sustainability and 3) socio-ecological approaches to Antarctic and Southern Ocean conservation, and one synthesis theme that seeks to facilitate the provision of timely scientific advice to support effective Antarctic conservation. Research outputs will address the most pressing environmental challenges facing Antarctica and offer high-quality science to policy and advisory bodies including the Antarctic Treaty Consultative Meeting, the Committee for Environmental Protection and the Scientific Committee of the Commission for the Conservation of Antarctic Marine Living Resources.
Edition: 2022/12/02 Publisher: Cambridge University Press
Keywords: Antarktis; Antarktistraktaten; Sørishavet; forvaltning; human impact; miljøvern